Aging Behaviour of Al-Mg-Si Alloys Subjected to Severe Plastic Deformation by ECAP and Cold Asymmetric Rolling. (21st August 2011) - Farè, S.; Lecis, N.; Vedani, M.
Abstract : A study was carried out on aging behaviour of a 6082 alloy processed by two different severe plastic deformation techniques: ECAP and asymmetric rolling. Both techniques were able to generate an ultrafine-grained structure in samples processed at room temperature. It was stated that severe straining promotes marked changes in the postdeformation aging kinetics. The peaks of β ′′/ β ′ transition phases were anticipated and of progressively reduced intensity over the coarse grained alloy. A further peak accounting for onset of recrystallization also appeared in the most severely deformed samples. Full consistency in peak shape and position was found when comparing materials processed by ECAP and asymmetric rolling. Isothermal aging treatments performed at 180°C revealed that in the severely deformed samples, aging became so fast that the hardness curves continuously decreased due to overwhelming effects of structure restoration. On the contrary, aging at 130°C offers good opportunities for fully exploiting the precipitate hardening effects in the ultrafine-grained alloy.